Protecting ancient water harvesting technologies in India: strategies for climate adaptation and sustainable development with global lessons - Jain, Shubham; Srivastava, Aman; Vishwakarma, Dinesh Kumar; Rajput, Jitendra; Rane, Nitin Liladhar; Salem, Ali; Elbeltagi, Ahmed (Frontiers in Water, 2024)
IntroductionAncient water harvesting systems, such as those from the Indus Valley Civilization (~3500 BCE), have been vital for irrigation and climate resilience, especially in arid regions. One such prominent system in South Asia, called tank irrigation, initially thrived through community management but declined post-independence due to colonial policies and neglect in Sri Lanka and India. This study evaluates current policy frameworks and rehabilitation programs to enhance the resilience of these systems in India, develop strategies for their protection and adaptation to climate change, and integrate global lessons for sustainable development.MethodsA systematic meta-analysis of grey literature was conducted to aggregate data on policy constraints. Policy analysis involved detailed investigations of relevant documents, regulations, and comparative analyses of frameworks at regional and national levels. Pilot projects on tank rehabilitation were assessed through reported case studies and field surveys to gauge impact. Thematic analysis was used to explore the global potential of these systems in climate resilience and overall environmental sustainability.ResultsThe analysis showed that pilot projects for tank rehabilitation had limited success in achieving sustainability under current climate conditions. Tank irrigation systems are crucial for adapting to extreme weather, including floods, droughts, and heat waves, replenishing groundwater, reducing soil erosion, and ensuring reliable water supplies. Traditional water harvesting technologies support 17 Sustainable Development Goals (SDGs), including clean water access, hunger reduction, gender equality, and climate action. Integrating AI and machine learning in water management benefits disaster response, while eco-tourism aids system maintenance and cultural awareness.DiscussionThe study underscores the need for policy reforms to enhance tank rehabilitation and institutional arrangements. It calls for increased beneficiary participation and constitutional recognition of current practices. Strategic, national-scale assessments and resilience targets are recommended to improve the effectiveness of such water harvesting systems in mitigating natural hazards and enhancing environmental services.